Preventive measures for safe and healthy work with improvised expolsive devices in multinational operations - Kovačević, Nenad V.; Dimitrijević, Nenad P. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Since the re-admission of the Republic of Serbia to the United Nations (UN), members of the Ministry of Defence (MoD) and the Serbian Armed Forces (SAF) have been engaged in multinational operations (MnOps). All countries which send their members to MnOps timely undertake measures so that individuals intended to participate in MnOps learn about the dangers of explosive devices, and prepare themselves for safe life and work in MnOps. One of the measures taken is to produce a brochure or a manual to help members of MnOps learn about the dangers of explosives in the particular territory and about general procedures in the event of encountering such danger.The main problem is the lack of literature as the essence of the training process and the preparation of individuals referred to MnOps. The paper combines the currently available literature with the experience of MoD and SAF members as well as foreign armed forces members previously engaged in MnOps regarding the preventive measures for safe and healthy work with explosives i.e. with a special kind of explosives - improvised explosive devices.
Keywords: multinational operations; safes; procedures; prevention; measuring; literature; explosives